Genetic variants of DNMT3A and systemic lupus erythematosus susceptibility. Issue 1 (January 2015) - Piotrowski, Piotr; Grobelna, Malwina K.; Wudarski, Mariusz; Olesińska, Marzena; Jagodziński, Paweł P.
Abstract Objectives. A significant increase in DNA methyltransferase 3A (DNMT3A) transcript levels has recently been demonstrated in peripheral blood mononuclear cells from systemic lupus erythematosus (SLE) patients as compared to healthy individuals. Methods. Employing high resolution melting curve analysis (HRM) and PCR-restriction fragment length polymorphism analysis, we assessed the frequency of five single nucleotide polymorphisms (SNPs) of this gene: rs2289195, rs7590760, rs13401241, rs749131 and rs1550117, situated in different linkage disequilibrium blocks of the DNMT3A gene in two hundred and fifty seven women with SLE and six hundred and twenty five controls. Results. The lowest p values of the trend test were observed for the DNMT3A -448A> G (rs1550117) SNP (ptrend = 0.0111). We also found that, in a dominant inheritance model, the DNMT3A -448A> G SNP may protect from SLE development [odds ratio (OR) = 0.494 (0.294–0.830), p = 0.0068, pcorr = 0.034]. Furthermore, we observed that the DNMT3A -448A > G SNP in dominant inheritance models may protect from immunologic manifestations of SLE [OR = 0.1753 (95% CI = 0.04976–0.6176, p = 0.0026, pcorr = 0.0468). Conclusions. Our study demonstrates that the DNMT3A -448A> G SNP might protect from SLE and its immunologic manifestations in a sample from the Polish population.